Salivary cortisol levels, but not salivary α‐amylase levels, are elevated in patients with rheumatoid arthritis irrespective of depression. (14th November 2013) - Kim, Hyoun‐Ah; Jeon, Ja‐Young; Koh, Bo‐Ram; Park, Sat‐Byul; Suh, Chang‐Hee
Abstract: Objectives: Stress is recognized as an important factor in the etiology of rheumatoid arthritis (RA). Therefore, we explored multiple aspects of stress in RA patients. Methods: Salivary cortisol and α‐amylase levels were measured as markers of the hypothalamic–pituitary–adrenal axis activity and sympatho‐adrenomedullary system activity, respectively. Depression was assessed by the Beck Depression Inventory (BDI) and short‐term analysis of the heart rate variability (HRV) was performed to evaluate the autonomic nervous system. Results: The salivary cortisol levels of the RA patients were significantly higher than those of the normal controls (NC; 0.12 ± 0.162 μg/dL vs . 0.068 ± 0.052 μg/dL, P = 0.006). There was no difference in salivary α‐amylase levels between the RA and the NC. The BDI levels of the RA patients were significantly higher than the NC (13.7 ± 8.9 vs . 6.4 ± 6.9, P < 0.001). Depression was more prevalent in RA patients than in the NC. The salivary cortisol levels were still significantly higher in the RA than the NC after controlling BDI by logistic regression analysis ( P = 0.002). There was no significant difference in the HRV of RA patients and the NC. The evaluation of relationship between stress measures and disease activity markers of RA revealed that only BDI was positively correlated with the visual analogue pain scale. Conclusion: Salivary cortisol levels and the BDI of RA patients were higher than those of the NC, and elevated salivary cortisol levels were independent of depression. However, the level of stress may not be correlated with disease activity in RA.